The given system is:
![\begin{gathered} 8x+11y=37 \\ 8x+y=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i5gm3oqa0wemzdve9wid5ycidinkkf5c2n.png)
Notice that the coefficients of x in both equations are the same.
Therefore, Subtract the first equation form the second to eliminate the variable x:
![\begin{gathered} 8x-8x+11y-y=37-7 \\ 10y=30 \\ y=(30)/(10)=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n3g19tm6vjw0ggx62ug8x0mdfzrkc37vef.png)
Substitute y = 3 into the second equation:
![\begin{gathered} 8x+3=7 \\ 8x=7-3=4 \\ x=(4)/(8)=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l3akwd383mxtkzmjh16f4xkt14q5o8jf6i.png)
Hence, the solution of the system is:
x = 1/2 and y = 3